Drawing-from-Memory in Constructional Apraxia: Effects of Focal Cortical Lesions on Performance - McCrea, Simon M.; Chomiak, Debbi L. (Journal of Psychology and Psychotherapy Research, 2015)
Constructional apraxia is impairment in activities such as building, assembling, and drawing. In this paper data is presented on the performance of left and right hemisphere single focal contiguous stroke lesion participants on drawing tasks of houses, trees, and persons. In this study, 41 participants completed a comprehensive neuropsychological battery including the House-Tree-Person Drawing Task. The drawings were then rated as exhibiting signs of neurological impairment or non-impairment by three evaluators that were blinded to the medical condition of the patient. The neuropsychological evaluator did not rate the drawings. There was 72% agreement between the three evaluators of the 123 drawings in their dichotomous ratings of constructional apraxia drawings. Both a group mean and case series analysis was used to examine the data and some patterns of concordance with a detailed cognitive neuropsychological model of constructional apraxia was found.